2017
DOI: 10.1292/jvms.16-0164
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenic characterization of <i>Erysipelothrix rhusiopathiae</i> Met-203 type SpaA strains from chronic and subacute swine erysipelas in Japan

Abstract: To characterize the Erysipelothrix rhusiopathiae Met-203 type surface protective antigen (Spa) A strains causing swine erysipelas in Japan, the nucleotide sequence of the hypervariable region of the spaA gene was determined in 80 E. rhusiopathiae (serotype 1a) isolates collected from pigs with chronic and subacute swine erysipelas in 14 prefectures in 2008–2014. In this study, 14 (17.5%) isolates were Met-203 type SpaA strains. We confirmed the pathogenicity of a Met-203 type SpaA strain in specific-pathogen-f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…It was previously found in a handful of pig isolates from Germany (n = 4) (Janßen et al, 2015). Otherwise, this variant has been mostly limited to strains from China ( Supplementary Table S2) and Japan, where it is widespread and has been isolated from pigs with acute, subacute and chronic infections Uchiyama et al, 2017) and where it appears to be increasing in prevalence (Ogawa et al, 2017). There is, however, not yet any evidence of this variant being associated with an increase in virulence (Zou et al, 2015).…”
Section: Spaa Diversity Correlation With Population Structure and Rmentioning
confidence: 97%
“…It was previously found in a handful of pig isolates from Germany (n = 4) (Janßen et al, 2015). Otherwise, this variant has been mostly limited to strains from China ( Supplementary Table S2) and Japan, where it is widespread and has been isolated from pigs with acute, subacute and chronic infections Uchiyama et al, 2017) and where it appears to be increasing in prevalence (Ogawa et al, 2017). There is, however, not yet any evidence of this variant being associated with an increase in virulence (Zou et al, 2015).…”
Section: Spaa Diversity Correlation With Population Structure and Rmentioning
confidence: 97%
“…Erysipelothrix rhusiopathiae is a zoonotic pathogen that causes erysipelas in a variety of animals and erysipeloid in humans . In Japan, the incidence of acute swine erysipelas has been increasing since 2008 . It has been reported that increased cases of acute swine erysipelas are associated with clonal strains belonging to a certain lineage of E. rhusiopathiae ; however, the reason for the increase in cases has been unclear, and it has not been determined whether these clonal strains are prevalent among only domesticated pigs or are widespread in wild animals.…”
Section: Prevalence (Positive Rate) Of Antibodies Against Erysipelothmentioning
confidence: 99%
“…Arthritis is a very common symptom of GPS infection. However, infections by other related pathogens, such as Streptococcus suis [4], Erysipelothrix rhusiopathiae [5, 6], Mycoplasma hyorhinis [7], Actinobacillus pleuropneumoniae [8] and Actinobacillus suis [9], also result in identical arthritis. Therefore, it is necessary to distinguish GPS infection from those caused by other pathogens allowing targeted treatment of the disease.…”
Section: Introductionmentioning
confidence: 99%